Processes of Translation and Interpreting from a Native into a Foreign Language: Psycholinguistic Aspects - Леонід Черноватий; Наталя Ковальчук (Психолінгвістика, 2020)
The aim of the paper deals with the preliminary verification of D. Gile’s (2009) hypothesis (Effort Model) concerning the dependence of the translation quality not only on the command of the two languages involved, but also on the degree of the translator’s or interpreter’s processing mechanism saturation.